Self-supported silver nanoparticles containing bacterial cellulose membranes - Barud, Hemane S. [UNESP]; Barrios, Celina [UNESP]; Regiani, Thais [UNESP]; Marques, Rodrigo Fernando Costa [UNESP]; Verelst, Marc; Dexpert-Ghys, Jeannette; Messaddeq, Younes [UNESP]; Ribeiro, Sidney José Lima [UNESP] (Elsevier B.V., 2008)
Hydrated bacterial cellulose (BC) membranes obtained from cultures of Acetobacter xylinum were used in the preparation of silver nanoparticles containing cellulose membranes. In situ preparation of Ag nanoparticles was achieved from the hydrolytic decomposition of silver triethanolamine (TEA) complexes. Scanning electron microscopy (SEM) images and X-ray diffraction (XRD) patterns both lead to the observation of spherical metallic silver particles with mean diameter of 8 nm well adsorbed onto the BC fibriles. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: bacterial cellulose; silver; cellulose membranes; silver membranes; X-ray diffraction; electron microscopy